Combination of serum PSA assay, multi-parametric MRI and targeted prostate biopsy for prostate cancer screening in Nanjing - Liang, Jing; Zhao, Xiao-Zhi; Shi, Jing-Yan; Qiu, Xue-Feng; Zhang, Qing; Zhuang, Jun-Long; Wang, Wei; Deng, Yong-Ming; Huang, Hai-Feng; Zhang, Cheng-Wei; Guo, Hong-Qian (Zhonghua nan ke xue, 2019)
To investigate the exact prevalence of PCa among males in Nanjing and search for a mode of PCa screening suitable for the specific conditions. From January to December 2018, we collected serum samples and clinical information from 6 903 men aged ≥50 years taking physical examination in 16 community health service centers in Nanjing. We proposed multi-parametric MRI (mpMRI) for those with serum PSA ≥4 μg/L, transperineal systematic biopsy and MRI/ultrasound fusion targeted prostate biopsy for those who scored ≥3 points on the Prostate Imaging-Reporting and Data System Version 2 (PI-RADS v2), transperineal systematic biopsy only for those with a PI-RADS v2 score of <3 and serum PSA ≥10 μg/L, and follow-up examinations every 6 months for those with a PI-RADS v2 score of <3 and serum PSA <4 μg/L. Among the 6 903 male subjects, 835 (12.1%) were found with serum PSA≥4 μg/L; 229 (77.4%) of the 296 men that received mpMRI scored ≥3 points on PI-RADS v2; and 79 (53.4%) of the 148 males that underwent prostate biopsy w